Effect of grinding process parameters on grinding force of aluminium alloys - Alexius, An'yan (2008)
Significant developments have recently been made in the grinding of metals. Many researches have been devoted to determining the effect of these grinding parameters towards grinding force. The aim of this project is to study the effect of grinding process parameters namely depth of cut, number of passes, and use of coolant on grinding force of aluminium alloy (AA6061-T6). A three component force transducer dynamometer (Kistler Model Type 5070) was used to measure grinding forces in this experiment. A full factorial experimental design was used as the approach for the design of experiment. Through the analysis of variance (ANOVA) conducted, it was found that the most significant parameter is the usage of coolant followed by depth of cut. Meanwhile, number of passes was found to be not significant. In conclusion, the grinding force values increased as the number of passes became higher in proportional to depth of cut. The grinding force also increased if running in dry condition.